The Importance of Low-Intensive Agricultural Landscape for Birds of Prey - Emanuel Ștefan Baltag; Viorel Pocora; Lucian Eugen Bolboaca; Constantin Ion (Land, 2021)
Low-intensive agricultural areas of Romania sustain high species diversity. Together with natural habitats, these areas are very important for European biodiversity. The ecosystem´s health is reflected in the predator status because of their position at the top of the trophic networks. The Common Buzzard (Buteo buteo) is the most common bird of prey species in Europe. During the first survey census conducted in Eastern Romania (2011–2012 breeding seasons), 8.55–10.35 breeding pairs/100 square km have been counted. The Common Buzzard density varies between breeding seasons and with differences in habitat structure. Their density is positively influenced by the density of forest edge and Simpson diversity index of habitats but is negatively influenced by the total habitat fragmentation and mean daily temperature. According to this analysis, the selection of breeding territories by common buzzards is positively influenced by a heterogeneous landscape in an area with low-intensive agriculture and with large areas of open habitats made up of natural or semi-natural vegetation.